The influence of Cyberloafing behavior, Work-life Balance and Work Environment on Building Construction Employee Performance - Purakusumah, Dony Ilham; Soegoto, Dedi Sulistiyo (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Human resources are the main driving force in the company, whether it is a trading or service company. Human resources who basically have the ability to help organizations achieve goals or profits should be encouraged and facilitated in such a way by the company to support the maximum performance of these human resources. Especially in building construction companies, typical work that requires excellent performance requires several factors that companies must consider to improve employee performance. Factors that can support it are work life balance and a good work environment, as with minimizing employee cyberloafing. The purpose of this study is to identify how employee performance is influenced by the influence of cyberloafing behavior (X1), work-life balance (X2) and work environment (X3) on employee performance (Y) at PT Binamitra Group. The sample of this study is 40 employees. stay PT. Binamitra Group. This type of research is explanatory research. Data collection was carried out by preliminary interviews and  questionnaires. Data were analyzed by linear regression. The results showed that: The results showed that cyberloafing behaviorhad a significant negative effect on employee performance, work-life balance had a significant positive effect on work performance, and the work environment had a significant positive effect on employee performance. Author's suggestion to improve employee performance at PT. The Binamitra Group can pay attention to this cyberloaping behavior which can result in a decrease in the performance of each of its employees.